Human rights, transnational actors and the Chinese government: Another look at the spiral model - Fleay, Caroline (Taylor Francis, 2006)
This article assesses the usefulness of Thomas Risse, Stephen Ropp and Kathryn Sikkink's spiral model as an explanation of the changes in the Chinese government's human rights practices from the time of the ‘anti-rightist’ campaign in 1957–1958 to the end of 2003. It is concluded that the spiral model has provided a valid explanation for many of the changes in the Chinese government's human rights practices, and its responses to its internal and external critics, over this time period. Many of the responses of the transnational human rights network and the Chinese government by the end of this period indicate that the latter had progressed to phase three of the model. It is also concluded that the spiral model only conceptualises part of the constitutive relationship between the target state and international human rights norms—the influence of these norms on the identities, interests and behaviours of a target state. It does not conceptualise the influence of a target state on international human rights norms or the transnational human rights network. Therefore, the spiral model cannot explain why the Chinese government has had such a significant influence over the enforcement mechanisms of these norms.